Calcinosis Cutis and Calciphylaxis in Autoimmune Connective Tissue Diseases - Ilaria Mormile; Francesca Mosella; Piergiorgio Turco; Filomena Napolitano; Amato de Paulis; Francesca Wanda Rossi (Vaccines, 2023)
Calcinosis represents a severe complication of several autoimmune disorders. Soft-tissue calcifications have been classified into five major types: dystrophic, metastatic, idiopathic, iatrogenic, and calciphylaxis. Autoimmune diseases are usually associated with dystrophic calcifications, including calcinosis cutis, occurring in damaged or devitalized tissues in the presence of normal serum levels of calcium and phosphate. In particular, calcinosis cutis has been described in dermatomyositis, polymyositis, juvenile dermatomyositis, systemic sclerosis, systemic lupus erythematosus, primary Sjögren’s syndrome, overlap syndrome, mixed connective tissue disease, and rheumatoid arthritis. Calciphylaxis, a severe and life-threatening syndrome presenting with vascular calcifications and thrombosis, has also been associated with some autoimmune conditions. Due to the potentially disabling character of calcinosis cutis and calciphylaxis, physicians’ awareness about the clinical presentation and management of these diseases should be increased to select the most appropriate treatment option and avoid long-term complications. In this review, we aim to analyze the clinical features of calcinosis cutis and calciphylaxis associated with autoimmune diseases, and the main treatment strategies evaluated up to now for treating this potentially disabling disease.